Laparoscopic Sleeve Gastrectomy in a Morbidly Obese Patient with Myasthenia Gravis: A Review of the Management - Megana Ballal; Tracey Straker (Case Reports in Medicine)
Myasthenia gravis, a disorder of neuromuscular transmission, presents a unique challenge to the perioperative anesthetic management of morbidly obese patients. This report describes the case of a 27-year-old morbidly obese woman with a past medical history significant for myasthenia gravis and fatty liver disease undergoing bariatric surgery. Anesthesia was induced with intravenous agents and maintained with an inhalational and balanced intravenous technique. The nondepolarizing neuromuscular blocker Cisatracurium was chosen so that no reversal agents were given. Neostigmine was not used to antagonize the effects of Cisatracurium. The goal of this approach was to reduce the risk of complications such as postoperative mechanical ventilation. The anesthetic and surgical techniques used resulted in an uneventful hospital course. Therefore, we can minimize perioperative risks and complications by adjusting the anesthetic plan based on the patient’s physiology and comorbidities as well as the pharmacology of the drugs.